Rules of Engagement as an Example of a Security Protocol Constituting a “Code of Conduct” in Military Operations - Marcin Marcinko (Politeja)
Rules of Engagement (ROE) constitute a structured framework guiding the use of lethal force within specific operational contexts, blending legal, policy and operational considerations. Primarily, they empower commanders to oversee military operations effectively while providing soldiers with clear directives for conduct on the battlefield. ROE align with the security protocol theory, defining a set of rules that rationalise and legitimise complex security measures and their enforcement. As a sui generis code of conduct, ROE function as a security protocol within military operations, serving as a normative system facilitating the implementation of legal and strategic objectives. Unlike generic protocols, ROE are intricately shaped by political goals, military requirements and legal norms, manifesting as detailed operational guidelines. Thus, ROE serve as a code facilitating the application of law and the pursuit of political and military aims during operations. This paper seeks to elucidate the nature and significance of ROE in contemporary warfare, exploring their compatibility with the security protocol model and examining any unique attributes that distinguish them within this framework.